Respuesta :

ok so according to comments, question is
[tex] -21\sqrt{27x^{9}} [/tex]
remember that
[tex] \sqrt{xy} [/tex]=[tex] \sqrt{x} [/tex] times [tex] \sqrt{y} [/tex]
and [tex] \sqrt{yx^{2}} [/tex]=[tex] x\sqrt{y} [/tex]
so
[tex] -21\sqrt{27x^{9}} [/tex]=[tex] -21\sqrt{27}\sqrt{x^{9}} [/tex] = [tex] -21\sqrt{9}\sqrt{3}\sqrt{x^{2}}\sqrt{x^{2}}\sqrt{x^{2}}\sqrt{x^{2}}\sqrt{x} [/tex]= [tex] -21(3)\sqrt{3}(x)(x)(x)(x)\sqrt{x} [/tex]=
[tex] -63x^{4}\sqrt{3}\sqrt{x} [/tex]=[tex] -63x^{4}\sqrt{3x} [/tex]